Realising Pancasila Industrial Relations In Terms Of The Muamalah Principle In Islam For The Period 2008-2015 - Achmad Basari; Hanief Saha Ghafur (Publikasi Indonesia, 2023)
Muamalah is the sunnatullah of man as a social being. One form of mammalian is in the form of employment relations. Labour relations in the modern era developed into industrial relations and experienced developments in form and scope. The Indonesian state based on Pancasila and the 1945 Constitution aspires to realise fair industrial relations formulated in Pancasila Industrial relations. On the other hand, the majority of Indonesia's population is Muslim and has fair industrial relations. Efforts to realise fair industrial relations through the approach of the Indonesian constitution, namely industrial relations and the approach of the mullah principle, can be juxtaposed. In the national context, the government formulated Pancasila Industrial Relations as the goal of developing and fostering Industrial Relations. The author will discuss the Islamic perspective on justice in industrial relations and the role of each in realising equitable industrial relations. The compatibility and differences between these approaches can be a dissolution to realising justice in industrial relations to its order and application